Critical literacy in intercultural contexts: the case of the Bilingual Primary School Emiliano Zapata - Vázquez Ahumada, María Andrea (2023)
This paper describes the experience of the project Los siete ratones ciegos dan la vuelta al mundo, developed in the Bilingual Elementary School Emiliano Zapata of Sector 02 of the Indigenous Education System from Puebla state (Mexico), and also how teachers, students, mothers and fathers, as well as collaborators from all over the world gathered to celebrate International Mother Language Day. At the same time, we propose a reflection on the implications both pedagogic and intercultural, as well as human, of a collective exercise. From the critical perspective of both literacy and discourse studies and linguistic diversity studies, we account how the school-academic, the literary and the personal identity, as well as the emotional, are articulated in a horizontal and transversal exercise of knowledge construction within intercultural education. Through the pedagogical exercise described, it was possible for the indigenous students of this school to shape their identity from the value of their first language in dialogue with other languages and not from the conception of a vulnerable group.